Microblogging and the Value of Undirected Communication - Buechel, Eva C.; Berger, Jonah (Journal of Consumer Psychology, 2018)
Online social networks have become extremely popular, but what drives sharing through these channels? We demonstrate that one of the most popular features of online social networks, microblogging (e.g., tweeting or sharing Facebook status updates), is driven in part by its undirected nature. Microblogging allows people to simultaneously express themselves to a large number of potential communication partners without having to address anyone in particular. As a result, this communication channel is particularly valued when people feel socially apprehensive; it allows them to reach out without having to impose communication and potentially bother anyone in particular. These findings shed light on one reason why people use online social networks and provide insight into the value of undirected communication.